1983
DOI: 10.1111/j.1365-2125.1983.tb01532.x
|View full text |Cite
|
Sign up to set email alerts
|

Disposition of chloroquine in man after single intravenous and oral doses.

Abstract: 1 Chloroquine was given in 300 mg single doses as an i.v. infusion, an oral solution and as tablets at intervals of at least 56 days to 11 healthy volunteers. Concentrations of chloroquine and its metabolite desethylchloroquine were measured in plasma, erythrocytes and urine using h.p.l.c.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

22
196
3
6

Year Published

1983
1983
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 224 publications
(227 citation statements)
references
References 10 publications
(7 reference statements)
22
196
3
6
Order By: Relevance
“…A two-compartment model was best fit with the concentration-time profiles of both CQ and DECQ, with a one transit compartment model for the absorption of CQ. This multiexponential decline in blood concentrations of both CQ and DECQ were in consistency with previous reports (Gustafsson et al, 1983;Aderounmu et al, 1986;Karunajeewa et al, 2008;Obua et al, 2008). The mean transit time of absorption (MTT: 0.773 h), peripheral volume of distribution (Vp: 1,600 l), and elimination halflife (t 1/2 : 10.7 days) of CQ were similar to the previously reported values in other populations, but systemic clearance (CL: 6.13 l/h) was relatively lower (FriskHolmberg et al, 1984;Aderounmu et al, 1986;Gustafsson et al, 1987;Tett et al, 1987;Edwards et al, 1988;Titus et al, 1989;Vries et al, 1994;Lee et al, 2008;Karunajeewa et al, 2008;Obua et al, 2008;Karunajeewa et al, 2010;Wetsteyn et al, 2012;Zhao et al, 2014).…”
Section: General Pharmacokinetic Propertiessupporting
confidence: 93%
“…A two-compartment model was best fit with the concentration-time profiles of both CQ and DECQ, with a one transit compartment model for the absorption of CQ. This multiexponential decline in blood concentrations of both CQ and DECQ were in consistency with previous reports (Gustafsson et al, 1983;Aderounmu et al, 1986;Karunajeewa et al, 2008;Obua et al, 2008). The mean transit time of absorption (MTT: 0.773 h), peripheral volume of distribution (Vp: 1,600 l), and elimination halflife (t 1/2 : 10.7 days) of CQ were similar to the previously reported values in other populations, but systemic clearance (CL: 6.13 l/h) was relatively lower (FriskHolmberg et al, 1984;Aderounmu et al, 1986;Gustafsson et al, 1987;Tett et al, 1987;Edwards et al, 1988;Titus et al, 1989;Vries et al, 1994;Lee et al, 2008;Karunajeewa et al, 2008;Obua et al, 2008;Karunajeewa et al, 2010;Wetsteyn et al, 2012;Zhao et al, 2014).…”
Section: General Pharmacokinetic Propertiessupporting
confidence: 93%
“…It remains the most widely used antimalarial agent although there is considerable concern surrounding its safety when given parenterally (WHO, 1984). Preliminary studies in volunteers (Gustafsson et al, 1983;Looareesuwan et al, 1986) showed that intravenous injection of chloroquine was potentially dangerous because of transient but very high, plasma chloroquine concentrations. It seemed likely that slow intravenous infusion of chloroquine would be safer.…”
Section: Discussionmentioning
confidence: 99%
“…In both healthy adults (Gustafsson et al, 1983) and children with uncomplicated falciparum malaria (Adelusi et al, 1982;Walker et al, 1983) the drug is well absorbed after oral administration and is detectable in the plasma for up to 52 days and in the urine for up to 119 days following oral or intravenous administration of a single dose (Gustafsson et al, 1983). Slow, rate-controlled intravenous infusion is an acceptable mode of administration for CQ in seriously ill patients or where oral therapy is not possible Edwards et al, 1987).…”
Section: Introduction Methodsmentioning
confidence: 99%
“…This has been shown clearly for alprenolol and imipramine (Piafsky & Borga, 1977). The high volume of distribution of chloroquine (Gustafsson et al, 1983) indicates extensive tissue binding but it is weakly bound in plasma, 46-74% in healthy individuals. This is in agreement with a previous report by Buchanan & van der Walt (1972).…”
Section: Discussionmentioning
confidence: 99%